Dialect Stigma and Group Conflicts - Salah KAOUACHE (Revue des Sciences Humaines)
As the quotation above indicates, social prejudices held on languages in general and dialects in particular are longstanding, and, despite the advance in the domain of sociolinguistics, they continue to exist. It seems that people do not see any reason to stop telling jokes and funny stories about regional dialects and evoking social stereotypes which go far beyond language itself. This problem exists as a product of society. The dialects of Liverpool and Birmingham, for instance, are vivid examples which are looked down in England. Similarly, the dialect of Jijel is a vivid example of the sort in Algeria.